Accounting Information, Creativity, and Education Influence on Culinary Business Success Moderated by Financial Literacy - Bintani, Ananda Chika; Nasrizal, Nasrizal; Rasuli, M.; Azlina, Nur; Silfi, Alfiati (Akuntansi & Ekonomika, 2025)
This study examines the effect of accounting information usage, creativity, and education level on the success of culinary SMEs in Pekanbaru, as well as the moderating role of financial literacy. SEM-PLS analysis on 132 SME actors reveals accounting information usage positively influences success by enabling better decision-making and operational efficiency through valuable, scarce resources per RBV theory, while creativity drives success via product innovation and competitive uniqueness; however, education level lacks impact as practical skills outweigh formal education in this context. Financial literacy strengthens the creativity-success link by helping implement innovative ideas strategically, but fails to moderate accounting usage due to its direct interpretability and education due to unrelated optimization needs. These findings stress prioritizing creativity, financial literacy, and accounting practices for SME sustainability.